Prohibition of discrimination based on religion, confession or worldview in the light of the provisions of the Labor Code - Majchrzak, Katarzyna (Prawo Kanoniczne, 2023)
The article presents issues related to the prohibition of discrimination in employment based on religion, confession or worldview. The study is based mainly on the provisions of the Labor Code and Polish and EU case law. The prohibition of discrimination strengthens the principle of equality before the law. Non-discrimination is one of the basic principles of labor law and at the same time it is one of the most important obligations imposed on the employer. There are two types of discrimination: direct and indirect. It does not constitute a violation of the principle of equal treatment in employment if religion, belief or belief is a real and necessary professional requirement.